Hemorrhagic Complications Following Abdominal Paracentesis in Acute on Chronic Liver Failure: A Propensity Score Analysis. Issue 49 (December 2015) - Lin, Su; Wang, Mingfang; Zhu, Yueyong; Dong, Jing; Weng, Zhiyuan; Shao, Lingyun; Chen, Jing; Jiang, Jiaji
Abstract : Abstarct: Patients with acute on chronic liver failure (ACLF) usually present with severe coagulopathy. Abdominal paracentesis is often performed in these patients. The aim of this study was to analyze the prevalence of hemorrhagic events after paracentesis and the predictive factors of this condition in ACLF populations. ACLF patients who underwent paracentesis were retrospectively enrolled within a 5-year period. A propensity score (PS) matching analysis was used to select matched cases from the overall nonhemorrhagic group to be used as the control group. Hemorrhagic complications and risk factors were examined using logistic regression analysis. A total of 602 abdominal paracenteses were carried out on 218 ACLF patients and 18 (2.99%) hemorrhagic complications were identified. The MELD scores were higher in hemorrhagic patients than overall patients before PS matching (25.77±6.65 vs 21.04 ± 7.93, P  = 0.013). We matched 18 cases with bleeding events to 72 unique cases without. The hemorrhagic group had significantly lower fibrinogen levels and higher PT levels than nonhemorrhagic cases. Logistic regression analysis revealed that lower fibrinogen levels could independently predict hemorrhagic complications (OR: 0.128, 95% CI: 0.023–0.697, P  = 0.017). The best cut-off value for reliable measurement of fibrinogen levels was 0.70 g/L, with a sensitivity of 76.4% and a specificity of 80.0%. The area under curve was 0.733 (95% CI 0.604–0.862, P value 0.002). Severe hemorrhagic complications occur more commonly in ALCF patients than previously thought. A low fibrinogen level is an independent predictor of bleeding events in patients with MELD >25.